Clinical Efficacy of Agnikarma in Karnini Yoni Vyapada Associated With Infertility – A Case Report - Sweta Raiyani; Shilpa Donga (International Journal For Multidisciplinary Research, 2026)
Introduction: Infertility is a multifactorial condition in which cervical factors, including chronic inflammation and abnormal tissue changes, play a significant role. Among various treatment modalities, Agnikarma, a parasurgical thermal cauterization procedure, is known for its ability to remove unhealthy tissue and alleviate chronic inflammation. Case Description: A 25-year-old female presented to the OPD of Prasuti Tantra and Stri-Roga at ITRA, Jamnagar, with complaints of per vaginal white discharge and itching in the vulval region, along with a history of primary infertility for one year. Clinical examination revealed significant cervical erosion with unhealthy mucosa, which was identified as a potential barrier to sperm transport. All other clinical and laboratory parameters were within normal limits. The condition was diagnosed as Karnini Yoni Vyapada. Intervention: The patient was initially managed with Yoni Prakshalana and during the first sitting to reduce local inflammation and improve the cervical environment. In the second sitting, following serological investigations, Agnikarma was performed on the cervix after 15 days under strict aseptic precautions. The procedure aimed to remove unhealthy cervical tissue and promote the regeneration of healthy mucosa. This was further supported by appropriate Ayurvedic management to optimize reproductive health and restore local balance. Outcome: On per speculum examination after three months of follow-up, complete healing of the cervical erosion was observed, along with restoration of normal cervical mucosa. Subsequently, after two months of Shamana Aushadhi, patient experienced a missed menstrual cycle. Pregnancy was confirmed through a urine pregnancy test and further ultrasonography revealed a viable single intrauterine pregnancy. Conclusion: This case demonstrates that Agnikarma is a highly effective, minimally invasive, and cost-efficient parasurgical intervention for managing cervical factors in infertility. It offers a viable alternative to conventional treatments for Karnini Yoni Vyapada, leading to successful conception.